Marijuana Legalization and Mental Health - Daniel Borbely; Otto Lenhart; Jonathan Norris; Agnese Romiti (Institute of Labor Economics (IZA), 2022)
This study examines the effects of U.S. state-level marijuana policies on mental health. Using data from three nationally representative data sets and estimating difference-in-differences models that account for the staggered implementation of both medical and recreational marijuana legislation, we evaluate the impact on marijuana use as well as two measures of mental distress. We show that marijuana laws have positive effects on marijuana use, but find no evidence for any effect on mental health on average. Nonetheless, null aggregate effects mask sharp heterogeneities across the age distribution. Our findings show that elderly individuals (age 60 and older) benefit from medical marijuana legalization in terms of better mental health, whereas legalizing recreational marijuana produces negative mental health effects for younger individuals (below age 35). The effects of medical marijuana legislation are driven by elderly people with pre-existing chronic health conditions, whereas those of recreational marijuana legislation are driven by younger and relatively healthy individuals. Furthermore, results are stronger for women than for men.
Keywords: I18; I10; K32; 330; marijuana legalization; recreational marijuana; medical marijuana; mental health